Digital Waste? Unintended Consequences of Health Information Technology - Petri Böckerman; Mika Kortelainen; Liisa T. Laine; Mikko Nurminen; Tanja Saxell (Institute of Labor Economics (IZA), 2019)
We exploit a large-scale natural experiment – the rollout of a nationwide electronic prescribing system in Finland – to study how digitization of prescriptions affects pharmaceutical use and health outcomes. We use comprehensive administrative data from patients treated with benzodiazepines, which are globally popular, effective but addictive psychotropic medications. We find no impact on benzodiazepine use on average, but among younger patients e-prescribing increases repeat prescription use. Younger patients' health outcomes do not improve but adverse outcomes, such as prescription drug abuse disorders and suicide attempts, increase dramatically. Improving access to medication through easier ordering may thus increase medication overuse.
Keywords: H51; H75; I12; I18; 330; health information technology; electronic prescribing; repeat prescriptions; inefficiency; medication overuse